No - the second row of your augmented matrix is incorrect.x1 − 2x2 − 8x3 = 0
3x1 + 2x2 + 0 = 0
augmented matrix:
[ 1 -2 -8 0 ]
2 2 0 0
-2R1 + R2
[ 1 -2 -8 0 ]
0 6 16 0
-1/6R1 + R2
[ 1 -2 -8 0 ]
0 1 8/3 0
Is this correct?
\(\displaystyle x_2= -\frac{3}{2}x_1= -\frac{3}{2}(2x_3)= -3x_3\)And what were those conclusions? What are \(\displaystyle x_1\), \(\displaystyle x_2\), and \(\displaystyle x_3\)?
Personally, I wouldn't use matrices at all. Perhaps I am just too "simple" for that! I would observe that adding the two equations immediately eliminates \(\displaystyle x_2\) leaving \(\displaystyle 4x_1- 8x_3= 0\) so that \(\displaystyle x_1= 2x_3\). And, of course, \(\displaystyle x_2= \frac{3}{2}x_1= \frac{3}{2}(2x_3)= 3x_3\). Taking \(\displaystyle x_3= a\), \(\displaystyle (x_1, x_2, x_3)= (2a, 3a, a)\).
Subhotosh, Prof Halls did get a non trivial solution (one you fix the minor error)No - the second row of your augmented matrix is incorrect.
For this homogeneous equation, only the trivial equation:
x1 = x2 = x3 = 0
is possible.